Women in economic activity : a global statistical survey (1950-2000) - OIT (Ginebra : OIT)
Profiles of working women--Trends in employment and unemployment in developing and developed countries (1976-1980)--Africa--Women in the economic activity in Africa--Asia--Women in the economic activity in Asia--Latin America and the Caribbean--Women in the economic activity in Latin America and the Caribbean--European market economy countries--Women in the economic activity in european market economy countries--North America--Women in the economic activity in North America--Oceania--Women in the economic activity in Oceania--Eastern Europe--Centrally planned economies (Eastern Europe).
Keywords: ESTADÍSTICAS ECONÓMICAS; MUJERES; TRABAJO; MANO DE OBRA; EMPLEO